Industry, firm, year and country effects on profitability in EU food processing - Jan Schiefer; Stefan Hirsch; Monika Hartmann; Adelina Gschwandtner (University of Kent, School of Economics, 2013)
We decompose the variance of food industry return-on-assets into industry, firm, year and country effects. After determining significance in a nested ANOVA, we estimate the magnitude using components of variance in a large sample of corporations. As a robustness check, we estimate a multilevel model that additionally allows us to estimate the impact of several covariates at each level. The results show that firm characteristics are more important than industry structure in determining food industry profitability. In particular, firm size seems to be an important driver of profitability while firm risk, age and, surprisingly market share have a negative influence.
Keywords: L00; C22; L66; 330; ROA; decomposition; variance components; MBV; RBV